POWER IN THE UNION. - Hall, Amy (New Internationalist)
The Debt Collective is a US-based union for debtors that aims to challenge illegitimate debt and build collective power. Founded by Astra Taylor, the Debt Collective brings together borrowers from across the US to advocate for debt cancellation and relief. The organization has been successful in organizing a student debt strike and has helped win changes to federal law, resulting in over $140 billion in student debt being written off since 2020. The explosion of household debt in the US is attributed to factors such as austerity measures, the privatization of essential goods and services, weakening labor rights, and financial sector deregulation. The Debt Collective emphasizes the power of debtors to take collective action through economic, legal, and moral means. Challenges in seeking unity as debtors include the differential impact of debt on different groups, such as Black women who are disproportionately burdened by student debt. The Debt Collective aims to bridge these divisions and build solidarity among various categories of debtors. The organization advocates for debt abolition and the need for reparative public goods to address historical and ongoing inequalities. Astra Taylor's latest book, "Solidarity: The Past, Present and Future of a World-Changing Idea," explores these themes further.